To catch a spy the art of counterintelligence - Olson, James M. 1941- (Georgetown University Press, 2021)
The United States is losing the counterintelligence war. Foreign intelligence services, particularly those of China, Russia, and Cuba, are recruiting spies in our midst and stealing our secrets and cutting-edge technologies. In To Catch a Spy: The Art of Counterintelligence, James M. Olson, former chief of CIA counterintelligence, offers a wake-up call for the American public and also a guide for how our country can do a better job of protecting its national security secrets. Olson takes the reader into the arcane world of counterintelligence as he lived it during his thirty-year career in the CIA. After an overview of what the Chinese, Russian, and Cuban spy services are doing to the United States, Olson gives a masterclass on the principles and practice of counterintelligence. Readers will learn his ten commandments of counterintelligence and about specific aspects such as running double-agent operations and surveillance. The book also analyzes twelve actual case studies in order to illustrate why people spy against their country, the tradecraft of intelligence, and where counterintelligence breaks down or succeeds. A "lessons learned" section follows each case study, and the book also includes an appendix of recommended further reading. This book will fascinate anyone with an interest in the real world of espionage